Methyltransferase-like 3 is a target for the diagnose and therapy of clear cell renal carcinoma - Dongqiong Xiao; Xiaojuan Su (Frontiers in Pharmacology)
Patients diagnosed with clear cell renal carcinoma (ccRCC) frequently exhibit metastatic disease, which complicates treatment strategies, underscoring the urgent need for mechanistic insights and early diagnostic biomarkers. Current research is dedicated to uncovering the mechanisms behind ccRCC development and resistance to treatment, with a particular focus on the role of methyltransferase-like 3 (METTL3) in RNA N6-methyladenosine modification, a key gene regulatory process. This review synthesizes current evidence on METTL3’s functions, revealing its oncogenic activity through m6A-mediated regulation of RNA stability and translation, which promotes tumor progression, metastasis, and chemoresistance. We further explore METTL3’s dual diagnostic and therapeutic relevance, including its utility as a prognostic biomarker and its targeting via novel strategies such as small-molecule inhibitors (e.g., Erianin) and combination therapies with mTOR or immune checkpoint inhibitors. By consolidating these advances, this review positions METTL3 as a critical node for advancing precision medicine in ccRCC.